2022
DOI: 10.1186/s12889-022-14029-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with COVID-19 vaccine intentions during the COVID-19 pandemic; a systematic review and meta-analysis of cross-sectional studies

Abstract: Background A high COVID-19 vaccine uptake is essential to achieve herd immunity to combat the current strain of COVID-19 and potential future variants. This review aimed to identify factors associated with public intention to receive COVID-19 vaccines until February 2021 to provide accessible data to policymakers to inform framing and targeting of messages designed to optimise vaccine uptake. Methods Medline, Embase, CINAHL, PsycINFO, PsycARTICLES,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 75 publications
(240 reference statements)
8
38
2
Order By: Relevance
“…Previous studies have shown an association between previous influenza vaccination and COVID-19 vaccine willingness and/or acceptance [6] , [7] . Our findings add to the literature, by confirming the association between influenza vaccination and vaccination for COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown an association between previous influenza vaccination and COVID-19 vaccine willingness and/or acceptance [6] , [7] . Our findings add to the literature, by confirming the association between influenza vaccination and vaccination for COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“…COVID-19 vaccine mandates are not well studied in the literature, but they were shown to be positively associated with COVID-19 vaccine uptake in the general population of Hong Kong and in the ethnic minorities in the Netherlands 32 , 36 . Recent studies have since questioned the impact of such policies in the long term 42 , 43 . Thus, differences in vaccine uptake between strata cannot be solely explained by the introduction of certificates.…”
Section: Discussionmentioning
confidence: 99%
“… 80 , 81 Furthermore, several research groups have aimed to assess the determinants of, and factors driving, vaccine hesitancy and acceptance. 82 , 83 Notably, many COVID-19 vaccine-associated studies have focused on healthcare workers (HCWs) in the early stages of the pandemic, because many countries prioritized vaccination of HCWs at the frontline of the pandemic response, who helped safeguard the lives of vulnerable populations. 84 …”
Section: Vaccine Development Against Covid-19mentioning
confidence: 99%